The Influence of Work Culture and Work Motivation on Teacher Performance - Muhammad Taqwim (Presscience, 2024)
A strong work culture and effective motivation are essential for optimizing teacher performance. This study examines the influence of work culture and work motivation on teacher performance, employing a literature review method to analyze scholarly articles from Google Scholar. The findings reveal that teacher performance is significantly influenced by organizational culture, leadership styles, and motivation strategies implemented within schools. A positive work environment enhances teacher commitment, job satisfaction, and productivity, while motivational factors, such as recognition, incentives, and leadership support, directly impact teachers’ enthusiasm and effectiveness in the classroom. The study further highlights that work-related stress can negatively affect performance, reinforcing the need for a supportive leadership approach that fosters engagement and professional growth. These insights contribute to the ongoing discourse on educational management and emphasize the need for schools to cultivate a strong work culture and motivational strategies to enhance teacher performance and overall educational outcomes.